5x+8-2x+26=0
3x=-26-8
3x=-34
3x/3=-34/3
x=-34/3 or -11.3
2x+5-10x+11=0
-8x=-11-5
-8x=-16
-8x/-8=-16/-8
x=2
2006-11-15 17:21:32
·
answer #1
·
answered by mich 2
·
0⤊
0⤋
5x+8-2x+26 = 3x + 34
2x+5-10x+11= -8x+16
2006-11-15 22:56:12
·
answer #2
·
answered by Chikk230 2
·
0⤊
0⤋
since 2x+5-10x+11=0 then 8x=16 x=2
so the answer of the formula is 5x+8-2x+26=3x+34=3*2+34=40
the answer is 40
2006-11-15 22:56:45
·
answer #3
·
answered by peterwan1982 2
·
0⤊
0⤋
5x+8-2x+26
=3x+34
2.2x+5-10x+11
=-8x+16
2006-11-15 22:56:05
·
answer #4
·
answered by raj 7
·
0⤊
0⤋
combining similar terms -8x + 16 = 0
-8x = -16
x= 2
simplify the second equation and substitute for the value of x
3x + 34 = 3(2) +34
= 6 + 34
= 40
2006-11-16 04:56:24
·
answer #5
·
answered by jdash01 3
·
0⤊
0⤋
5x+8-2x+26 (without an = this is not an equation all we can to is simplify)
3x+34
2x+5-10x+11=0
-8x+16=0
-8x+16-16=0-16
-8x+-16
-8x/-8=-16/-8
x=2
2006-11-15 23:04:19
·
answer #6
·
answered by barksabit 6
·
0⤊
0⤋
first one: (I am going to assume that equation equals zero)
5x+8-2x+26=0
consolidate like numbers
5x-2x+8+26=0
3x+34=0
get the x alone on one side
3x+34-34= 0-34
3x= -34
3x/3 = -34/3
x= 11.333333
Second one:
2x+5-10x+11=0
Consolidate like numbers
2x-10x+5+11=0
-8x+16=0
Get x alone on one side
-8x+8x+16=0+8x
16=8x
16/8= 8x/8
2=x
x=2
2006-11-15 23:00:23
·
answer #7
·
answered by Metaspy 3
·
0⤊
0⤋
i dont know the first one because what is it suppose to equal to, unless you are suppose to put it in simplest form. If so, then it is 3x+34
for the second one:
2x+5-10x+11=0 write it out
-8x+16=0 combine like terms
-8x=-16 subract both sides
x=2 divide
2006-11-15 22:58:06
·
answer #8
·
answered by lakersforlife 3
·
0⤊
0⤋
The lower one, you just sum the x's together (2x-10x), then sum the integers (5+11), and then move the integers to the otehr side of the equation. Then divide whatever you get on the opposite side of the equation from "x" by the number of x's you have left.
The top one has no "=" sign in it so I assume you use the "x" value you get from the bottom and put it into the top, and "plug-n-chug"
2006-11-15 22:56:32
·
answer #9
·
answered by Pete D 2
·
0⤊
0⤋
the first one needs to equal something but the second one x = 2. it comes from combining the x terms on the left side to equal -8x and put the constant terms on the right side to equal -16 (-11-5=-16). then divide each side by -8 to get x = 2.
2006-11-15 22:56:02
·
answer #10
·
answered by Pez 1
·
0⤊
0⤋